Relationship Between Nursing Services and Level of Satisfaction of Inpatients - Supriatna, Dadang; Rasmun, Rasmun; Kadir, Abd (Jurnal KESANS : Kesehatan dan Sains, 2023)
Introduction: One indicator of the success of individual health services at the Public Health Center is patient satisfaction. The provision of quality health services will provide satisfaction for the patient which has an effect on the patient's desire to return to an institution that provides effective health services. Patients will always seek health services in facilities whose health service performance can meet patient expectations. Health services that are not in accordance with patient expectations are expected to be input for health service organizations to try to fulfill them. Objective: To determine the relationship between nursing services and the level of satisfaction of inpatients at the Bongan Health Center, West Kutai Regency. Methods: This study uses an analytical descriptive type of research with a cross sectional approach which was carried out in April 2022. Results and Discussion: Nursing services in the sufficient category (87.5%). The satisfaction level of inpatients is in the satisfied category (45.8%). The relationship between nursing services and the level of satisfaction of inpatients is obtained p-value=0.014. Smaller than 0.05. Conclusion: There is a relationship between nursing services and the level of satisfaction of inpatients at the Bongan Health Center, West Kutai Regency